Pengaruh Kepemilikan Manajerial, Kepemilikan Institusional dan Kebijakan Hutang Terhadap Nilai Perusahaan - Fella Eka Darmayanti; Fauji Sanusi (FEB Universitas Sultan Ageng Tirtayasa, 2018)
The purpose of this study was to determine the effect of managerial ownership on firm value, to determine the effect of institutional ownership on the value of the company, to determine the policy of debt to firm value. In this study the method used to analyze is the method of library study and documentation study. While the research design used is basic research, causality, and quantitative. The sample of this study were 12 companies so that the data obtained were 60 data. The data used is secondary data. Data analysis uses classical assumption test, multiple regression, and partial test (t test). Based on the results of the analysis using IBM SPSS 22 software it is known that the role of dividend policy in mediating the value of the company using multiple linear regression equation is Y = 1.883 + 0.100KM + 0.393KI + (-4.210) DER + 0.224 which means that: 1) managerial ownership is influential positive for PBV with t count> t table (4.024> 1.67203) and sig value (0.000 <0.05). 2) institutional ownership has a positive effect on PBV thitung <t table (1,485 <1,67203) and sig value (0,143> 0,05). 3) debt policy (DER) has a negative effect on PBV with -thitung> -table (-2.994> -1.67203) and sig value (0.004> 0.05).